Myotonic dystrophy type 1 with diabetes mellitus, mixed hypogonadism and adrenal insufficiency. (18th January 2018) - Takeshima, Ken; Ariyasu, Hiroyuki; Ishibashi, Tatsuya; Kawai, Shintaro; Uraki, Shinsuke; Koh, Jinsoo; Ito, Hidefumi; Akamizu, Takashi
Summary: Myotonic dystrophy type 1 (DM1) is an autosomal dominant multisystem disease affecting muscles, the eyes and the endocrine organs. Diabetes mellitus and primary hypogonadism are endocrine manifestations typically seen in patients with DM1. Abnormalities of hypothalamic–pituitary–adrenal (HPA) axis have also been reported in some DM1 patients. We present a case of DM1 with a rare combination of multiple endocrinopathies; diabetes mellitus, a combined form of primary and secondary hypogonadism, and dysfunction of the HPA axis. In the present case, diabetes mellitus was characterized by severe insulin resistance with hyperinsulinemia. Glycemic control improved after modification of insulin sensitizers, such as metformin and pioglitazone. Hypogonadism was treated with testosterone replacement therapy. Notably, body composition analysis revealed increase in muscle mass and decrease in fat mass in our patient. This implies that manifestations of hypogonadism could be hidden by symptoms of myotonic dystrophy. Our patient had no symptoms associated with adrenal deficiency, so adrenal dysfunction was carefully followed up without hydrocortisone replacement therapy. In this report, we highlight the necessity for evaluation and treatment of multiple endocrinopathies in patients with DM1. Learning points: DM1 patients could be affected by a variety of multiple endocrinopathies. Our patients with DM1 presented rare combinations of multiple endocrinopathies; diabetes mellitus, combined form of primary and secondary hypogonadism and dysfunction of HPA axis. Testosterone treatment of hypogonadism in patients with DM1 could improve body composition. The patients with DM1 should be assessed endocrine functions and treated depending on the degree of each endocrine dysfunction.